A hard real-time robot communication approach based on preemptive CSMA/CA - Ying Zou; Tianmiao Wang; Hongxing Wei; Miao Liu (2011 6th IEEE Conference on Industrial Electronics and Applications, 2011)
In the cooperative interaction between multiple complex robots, preemption capability in real-time communication is critical. However, the applications of universal approaches have the limitation in robot communications. In this paper, an improved approach is presented based on preemptive CSMA/CA (Carrier Sense Multiple Access/Collision Avoidance) method to boost the real-time capability in the priority-based transmission. By analyzing the influencing factors of real-time capability in multi-robot communication, the improved approach of preemptive CSMA/CA is presented, the corresponding protocol is designed in robot network application, and then the node module is implemented based on ARM processor. Finally, experimental scheme and platform are designed, and the result establishes that the improved preemptive approach is better than CSMA/CD (Carrier Sense Multiple Access/Collision Detect) in priority-based transmission.